Substitusi Butiran Kering Destilat Pada Formulasi Pakan Puyuh Terhadap Kandungan Kimia Feses - A. Wardah; Tiurma Wiliana Susanti Panjaitan (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2019)
The aim of this research is to evaluate the effect of distiller dried grain (DDG) of rice husk in quail feed which effectively reduces important chemical elements in feces. The results showed that administration of DDG influenced the absorption of nutrients carbon, nitrogen, phosphorus and calsium in the quail intestine. Substitution of 10% DDG proportion in quail formulation not significantly (P>0.05) effect on carbon content in feces. Carbon content infeces of quail at proportion of 20% DDG were significantly (P<0.01) higher than 10%. Nitrogen content in feces of quail at proportion of 20% DDG significant (P<0.05) higher than both 10 and 0%.Futhermore nitrogen content in quail feces at 10% DDG significant (P<0.05) higher than 0%. Phosphorus content in feces quails at proportion of 10 and 20% DDG significantly (P<0.05) lower than 0%. Calcium content in quail feces at 10% and 0% not significant (P>0.05) but both were significantly (P<0.05) lower than 20%. The results of this study can be concluded that the substitution of 10% DDG of rice husk in quail feed formulations can increase absorption of phosphorus but decreases the absorption of carbon, nitrogen and calcium Keyword: chemical elements, distillater dried grain, feces, quail